Screening a nation for hepatitis C virus elimination: a cross-sectional study on prevalence of hepatitis C and associated risk factors in the Rwandan general population. Issue 7 (3rd July 2019) - Umutesi, Justine; Liu, Carol Yingkai; Penkunas, Michael J; Makuza, Jean Damascene; Ntihabose, Corneille K; Umuraza, Sabine; Niyikora, Julienne; Serumondo, Janvier; Gupta, Neil; Nsanzimana, Sabin
Abstract : Objectives: We analysed data collected during programmatic screening activities conducted in 2017 to describe hepatitis C virus (HCV) seroprevalence in the general population and identify associated factors. Design: We analysed data collected between June and September 2017. For both seroprevalence and viraemia, variations across demographic and geographic factors were assessed and multivariate regression models were fit to identify factors independently associated with each marker. Geospatial data were examined for visualisation. Setting: HCV screening was organised within each of the 30 districts in Rwanda. One designated location in each district was selected as the screening site and screening took place for 1 week at each site. Participants: This study included 124 223 male and female volunteers. Anti-HCV-positive individuals were followed up with HCV RNA viral load (VL) testing for infection confirmation. Main outcome measures: Two markers were examined: the presence of HCV antibodies and HCV RNA VL. Results: Among 124 223 individuals screened, 11 003 (8.86%, 95% CIs: 8.70% to 9.02%) were positive for anti-HCV. Anti-HCV prevalence varied by age with the oldest age group (>55 year olds) having a prevalence of 16.46% (95% CIs: 16.14% to 16.80%) and the youngest age group (<25 year olds) having a prevalence of 2.20% (95% CIs: 1.93% to 2.50%) (crude OR=8.78). After adjustment for covariates, an association remained between anti-HCV prevalence and age (p<0.001), province (p<0.001) and socioeconomic status (p<0.001). Of the 3771 anti-HCV-positive individuals who had an available HCV RNA VL result, 2099 (55.66%, 95% CI: 54.06% to 57.25%) had a detectable HCV RNA VL. Age was also associated with HCV viraemia (p<0.001). Conclusion: Results suggest that over 55% of individuals who screened positive for HCV-antibodies were chronically infected. Targeted screening for HCV among older individuals is recommended, given the association between age and infection. Further geographical hotspots of HCV infection can also inform targeted screening as Rwanda moves towards HCV elimination.